Chronic Pancreatitis Is Characterized by Distinct Complication Clusters That Associate With Etiological Risk Factors. (April 2019) - Olesen, Søren S.; Nøjgaard, Camilla; Poulsen, Jakob L.; Haas, Stephan L.; Vujasinovic, Miroslav; Löhr, Matthias; Lindkvist, Björn; Bexander, Louise; Gulbinas, Antanas; Kalaitzakis, Evangelos; Ebrahim, Mohamed; Erchinger, Friedemann; et al.
Abstract : OBJECTIVES: Chronic pancreatitis (CP) is characterized by several disease-related complications and multiple etiological risk factors. Past studies of associations between complications and risk factors have mostly been limited to single complications or highly focused on single etiologies. Using an objective data-driven approach (cluster analysis), we characterized complication clusters and their associations with etiological risk factors in a large cohort of patients with CP. METHODS: This was a multicenter, cross-sectional study including 1, 071 patients with CP from the Scandinavian and Baltic countries. Complications to CP were classified according to the M-ANNHEIM system, and treelet transform was used to derive complication clusters. Cluster complication frequencies were analyzed for their association with main etiological risk factors (smoking and alcohol). RESULTS: The mean age of participants was 57 years and 66% were men. Alcohol (55%) and smoking (53%) were the most common etiological risk factors and seen in combination in 36% of patients. Cluster analysis identified 3 distinct complication clusters characterized by inflammation, fibrosis, and pancreatic insufficiencies. An independent association between inflammatory complications and alcoholic etiology was seen (odds ratio [OR] 2.00 [95% CI [confidence interval], 1.38–2.90], P < 0.001), whereas smoking was associated with fibrosis-related complications (OR 2.23 [95% CI, 1.56–2.3.20], P < 0.001) and pancreatic insufficiencies (OR 1.42 [95% CI, 1.00–2.01], P = 0.046). DISCUSSION: Three distinctive clusters of complications to CP were identified. Their differing associations with alcoholic and smoking etiology indicate distinct underlying disease mechanisms.